Deep genetic divergence and paraphyly in cryptic species of Mugil fishes (Actinopterygii: Mugilidae). Issue 2 (17th February 2020) - Neves, Jessika M. M.; Almeida, JoÃo P. F. A.; Sturaro, Marcelo J.; FabrÉ, Nidia N.; Pereira, Ricardo J.; Mott, TamÍ
Abstract : Morphological conservatism among closely related species often results in incongruent taxonomic classification between studies, leading to disagreements about the inferred evolutionary history of the species. This is the case in Mugil fishes, where extreme morphologic conservatism contrasts with wide distributions and high genetic divergence. To understand how these morphologically similar species evolved, it is necessary to 1) test whether taxonomically recognized species are independently evolving lineages, and 2) evaluate the timing and geographic context of the diversification of these lineages. Based on three mitochondrial genes and fossil data, we estimated a comprehensive time-calibrated phylogeny for 13 out of the 16 valid species of Mugil and tested the monophyly of each species. Our results indicate that the diversification of Mugil began nearly 30 MYA, during a period of large temperature fluctuations. Mugil cephalus, M. curema and M. rubrioculus all form relatively old groups (between 5 and 10 MYA) and form paraphyletic entities. Our study reinforces the general finding that morphologically and ecologically similar species may have long and independent evolutionary histories, which must be considered when assessing the evolution and conservation of such ecologically and economically important species.